Experimental study of damage to ultra-high performance concrete slabs subjected to partially embedded cylindrical explosive charges. (October 2022) - Fan, Yi; Chen, Li; Yu, Runqing; Xiang, Hengbo; Fang, Qin
Highlights: Subjected ultra-high performance concrete slabs to partially embedded explosives. Measured the sizes of the resulting ejection and spalling craters. Evaluated the accuracy of four existing damage forecasting methods. Existing methods failed to account for explosive shape and embedment. A suggested estimation of the cone slope angle is 60°. Abstract: In this study, long and thin cylindrical charges were partially embedded in ultra-high-performance concrete (UHPC) and normal-strength concrete (NSC) slabs to investigate the damage characteristics of UHPC slabs subjected to explosions by conventional weaponry. The sizes of ejection and spalling craters were recorded after the experiment to compare the obtained data with the concrete slab damage characteristics predicted by current damage forecasting methods. The current damage forecasting methods were found to be unsuitable for the conditions considered in this study as they do not account for the effects of the explosive shape and depth of embedment (DOE) simultaneously. The results of the experiment using partially embedded charges indicated that the damage on the sides of the slabs decreased with decreasing slab thickness; the use of UHPC without fiber reinforcement instead of using NSC significantly increased the compressive strength but decreased the ability of the concrete structure to resist spalling damage; furthermore, a suggested estimation of the cone slope angle is 60° for theoretical analyses and the design of numerical simulation or field experiments.